Unauthorized Possession of Narcotic Drugs by Minors in Serbia: Analysis of Trends and (In)Effectiveness of the Criminal Law Response - Kovačević, Milica (Zbornik Instituta za kriminološka i sociološka istraživanja, 2026)
Narco-criminality and addiction have been one of the insurmountable social problems for decades. Unfavorable global tendencies are also present in Serbia, where criminal acts related to the abuse of narcotics represent a non-negligible share of the total criminality. Of particular concern is the increased number of minors who are prosecuted for drug-related crimes, as well as the number of young people who are identified as problematicic users, and therefore in need for appropriate interventions. The paper is dedicated to a summary overview of the effects of the legal solutions applied so far in Serbia, and in order to indicate the directions of future strategic action. The normative logical method has been applied, as well as the method of descriptive statistics when analyzing the available statistical data. The author concludes that the insistence solely on criminal legal reaction does not produce the desired results, considering that extremely complex problems related to drug abuse and addiction cannot be solved by reliance on repression.